Neuronal Activity in the Sciatic Nerve Is Accompanied by Immediate Cytoskeletal Changes - Yehuda, Bossmat; Gradus Pery, Tal; Ophir, Efrat; Blumenfeld-Katzir, Tamar; Sheinin, Anton; Alon, Yael; Danino, Noy; Perlson, Eran; Nevo, Uri (Frontiers in Molecular Neuroscience, 2021)
Mechanical events and alterations in neuronal morphology that accompany neuronal activity have been observed for decades. However, no clear neurophysiological role, nor an agreed molecular mechanism relating these events to the electrochemical process, has been found. Here we hypothesized that intense, yet physiological, electrical activity in neurons triggers cytoskeletal depolymerization. We excited the sciatic nerve of anesthetized mice with repetitive electric pulses (5, 10, 100 Hz) for 1 and 2 minutes and immediately fixed the excised nerves. We then scanned the excised nerves with high-resolution transmission electron microscopy and quantified cytoskeletal changes in the resulting micrographs. We demonstrate that excitation with a stimulation frequency that is within the physiological regime is accompanied by a significant reduction in the density of cytoskeletal proteins relative to the baseline values recorded in control nerves. After 10 Hz stimulation with durations of 1 minute and 2 minutes, neurofilaments density dropped to 55.8% and 51.1 % of the baseline median values, respectively. In the same experiments, microtubules density dropped to 23.7% and 38.5% of the baseline median values, respectively. These changes were also accompanied by a reduction in the cytoskeleton-to- cytoplasm contrast that we attribute to the presence of depolymerized electron-dense molecules in the lumen. Thus, we demonstrate with an in-vivo model a link between electrical activity and immediate cytoskeleton rearrangement at the nano-scale. We suggest that this cytoskeletal plasticity reduces cellular stiffness and allows cellular homeostasis, maintenance of neuronal morphology and that it facilitates in later stages growth of the neuronal projections.